THE EFFECT OF RED GUAVA JUICE ON HEMOGLOBIN LEVELS IN PREGNANT WOMEN DURING THE SECOND TRIMESTER AT PANCASILA PRIMARY CLINIC ,BATURETNO WONOGIRI - Afriani, Maria; Wijayanti, Wijayanti; Maharani P, Ajeng (Journal of Advanced Nursing and Health Sciences, 2024)
Background : The prevalance of anemia in Indonesia reaches 48.9%, attributed to various factors such as iron malabssorption. Therefore, additional vitamin C is required to improve the absorption of FE tablet consumption.Research Objective: The study aimed to examine the effect of red guava juice on improving hemoglobin levels during the second trimester of pregnant women at Pancasila Primary Clinic Wonogiri. Research Method : The research employed an experimental method with a pretest-posttest design with the control group. The sampling technique used total sampling involving 44 responden, divided into experimental groups (22 respondents) and control group (22 respondents).Research Results: The sstatistical analysis using the paired sample t -test revealed a Pvalue of 0,004 < 0.005 in the control group and 0.000 < 0.005 in the experimental group. In addition , the independepnt t-test demonstrated a P value of 0.002 < 0.005, indicatinga significant effect of red guava juice on improving hemoglobin levels. Conclusion: Based on the study development, red guava juice evoled as valuable therapeutic option for increasing hemoglobin levels during pregnancy, wether used independenly or in combination with iron ( FE ) tablets.